2018
DOI: 10.1504/ijmda.2018.096076
|View full text |Cite
|
Sign up to set email alerts
|

Global affective computing research in the period 1997-2017: a bibliometric analysis

Abstract: Notable fallouts in marketing and financial market prediction have raised the interest by the scientific community and the business world in Affective Computing (AfC). Automatically recognizing and responding to a user's affective states, AfC shows a great potential to improve companies capabilities of customer relationship management. The aim of this study is to evaluate this filed of research during the last twenty years, identifying for one side its evolution, by the major publications, citations, journals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…According to Ho et al [31], the annual growth rate of published papers is 12.5%. Pestana et al [32] found that publications double every 4 years. Thus, Affective Computing is attracting more and more researchers every year which could potentially foster diversity in a natural way.…”
Section: Diversity Studies In Affective Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ho et al [31], the annual growth rate of published papers is 12.5%. Pestana et al [32] found that publications double every 4 years. Thus, Affective Computing is attracting more and more researchers every year which could potentially foster diversity in a natural way.…”
Section: Diversity Studies In Affective Computingmentioning
confidence: 99%
“…Diversity analyses of the Affective Computing research community are scarce. There are some recent bibliometric studies analysing the past two decades of publications in the field [30], [31], [32] but, rather than on community members, they focus on identifying major publications, leading journals, key research topics, and most productive authors, institutions and countries in terms of number of published papers. They present nevertheless interesting findings directly or indirectly related to diversity as follows.…”
Section: Diversity Studies In Affective Computingmentioning
confidence: 99%
“…According to Ho et al [26], the annual growth rate of published papers is 12.5%. Pestana et al [27] found that publications double every 4 years. Thus, Affective Computing is attracting more and more researchers every year which could potentially foster diversity in a natural way.…”
Section: Diversity Studies In Affective Computingmentioning
confidence: 99%
“…Diversity analyses of the Affective Computing research community are scarce. There are some recent bibliometric studies analysing the past two decades of publications in the field [25], [26], [27] but, rather than on community members, they focus on identifying major publications, leading journals, key research topics, and most productive authors, institutions and countries in terms of number of published papers. They present nevertheless interesting findings directly or indirectly related to diversity as follows.…”
Section: Diversity Studies In Affective Computingmentioning
confidence: 99%
“…Some recent bibliometric studies have analyzed the past 20-25 years of publications in the field of Affective Computing, from 1995 to 2020 [2], [14], [15]. They all follow a similar methodology, searching for publications using the keyword "Affective Computing" in Web-of-Science (WoS), an online subscription-based scientific citation indexing service.…”
Section: Related Work a Bibliometric Studies On Affective Computingmentioning
confidence: 99%